2008
DOI: 10.1038/ijo.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary adherence and weight loss success among overweight women: results from the A TO Z weight loss study

Abstract: Background: Dietary adherence has been implicated as an important factor in the success of dieting strategies; however, studies assessing and investigating its association with weight loss success are scarce. Objective: We aimed to document the level of dietary adherence using measured diet data and to examine its association with weight loss success. Design: Secondary analysis was performed using data from 181 free-living overweight/obese women (mean ± s.d. age ¼ 43 ± 5 years, body mass index ¼ 31 ± 4 kg m À2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 27 publications
2
155
1
5
Order By: Relevance
“…According to [22], common failure in following traditional weight loss strategies among overweight and obese people has prompted a surge in alternative diet approaches like carbohydrate restriction (Atkins), fat restriction (Ornish) or replacing carbohydrate with protein (Zone). However, without proper weight loss strategy, losing weight is rather difficult to achieve.…”
Section: J Fundam Appl Sci 2017 9(4s) 905-919 913mentioning
confidence: 99%
“…According to [22], common failure in following traditional weight loss strategies among overweight and obese people has prompted a surge in alternative diet approaches like carbohydrate restriction (Atkins), fat restriction (Ornish) or replacing carbohydrate with protein (Zone). However, without proper weight loss strategy, losing weight is rather difficult to achieve.…”
Section: J Fundam Appl Sci 2017 9(4s) 905-919 913mentioning
confidence: 99%
“…16,32,33 These trials suggest that dietary adherence and caloric restriction are more important than macronutrient composition in determining weight loss (level I evidence). Canadian guidelines on obesity recommend a highprotein or low-fat diet as a reasonable short-term (6-12 mo) treatment option for adults with obesity (level III evidence).…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…At the end of 6 months, 12 months, and 2 years, the weight loss was similar for all 4 diets. The principal determinant of success was adherence to the diet, a finding made by Dansinger et al 13 and Alhassan et al 18 …”
Section: Comparison Of Diets With Different Macronutrient Compositionmentioning
confidence: 93%
“…In this study, too, a post-hoc analysis showed that adherence was the best predictor for weight loss and that the level of adherence to any diet was not very good. 18 Two reasons are proposed for the differences. First, the study by Gardner and colleagues 14 had a more homogeneous population, including only premenopausal women.…”
Section: Comparison Of Diets With Different Macronutrient Compositionmentioning
confidence: 99%